AB0881 Biologic Disease Modifying Anti-Rheumatic Drug Use in the Treatment of Juvenile Idiopathic Arthritis: Data from the Rheumatic Diseases Portuguese Register, Reuma.Pt. (10th June 2014) - Mourão, A.F.; Santos, M.J.; Melo Gomes, J.A.; Martins, F.M.; Ramos, F.; Fernandes, S.; Salgado, M.; Guedes, M.; Carvalho, S.; Costa, J.A.; Duarte, C.; Brito, I.; et al.
Abstract : Background: The Portuguese Society of Rheumatology developed the Rheumatic Diseases Portuguese Register (Reuma.pt) encompassing also Juvenile Idiopathic Arthritis patients followed by rheumatologists and pediatricians. Objectives: 1. To obtain an overview of biological agents use in Portuguese children with JIA. 2. To assess the effectiveness and safety of biological therapy at 6 months and 1 year of treatment. Methods: We retrieved data from Reuma.pt, until December 2013. We collected baseline patient and disease characteristics of patients with JIA who started treatment with biological agents. Follow-up data were analyzed and are presented at 6 months and 1 year. Disease activity was assessed using the number of active joints, ESR and CHAQ. Results: 812 patients with JIA, 227 received biological therapy.The mean age at disease onset of patients treated with biologic DMARDs was 6.9±4.7years and the mean age for starting biological therapy was 16.1±9.4years. The most common JIA categories were polyarticular RF negative (23.3%), polyarticular RF+(17.5%) and extended oligoarticular (16.0%).The median duration of the first biological agent was 5.76years. Most patients were treated with antiTNF as first line (90.3%):etanercept 69.2%, adalimumab 12.8%, infliximab 8.4%. Mean baseline active joint count was 5.1±5.8, decreasing to 1.2±2.4 and 1.0±3.1 after 6 months and 1 year of therapy. Mean ESR was 33.9±25.3 mm/1 sth and 26.9±23.9 and 19.1±180 after 6 months and 1 year. CHAQ decreased from 0.8±0.7 to 0.4±0.5 and 0.4±0.5 at 6 months and 1 year. 14.1% switched once to other biological therapy (3.08% in the first 6 months, 4.4% in the first year), 5.73% switched twice (0.88% in the first 6 months, 1.76% in the first year) and 2 patients (0.88%) switched 3 times after the first year of treatment. 14 serious adverse events were reported leading to discontinuation of the treatment, 6 in the first 6 months and 8 in the first year of treatment. There were no reported deaths. The one-year treatment retention with biological agents was 91%. Conclusions: JIA patients treated with biologics and registered in Reuma.pt showed a good profile of effectiveness and safety at 1 year. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3142